2003
DOI: 10.1074/jbc.m305857200
|View full text |Cite
|
Sign up to set email alerts
|

μ-Opioid Receptor Desensitization

Abstract: It is generally accepted that the internalization and desensitization of -opioid receptor (MOR) involves receptor phosphorylation and ␤-arrestin recruitment. However, a mutant MOR, which is truncated after the amino acid residue Ser 363 (MOR363D), was found to undergo phosphorylation-independent internalization and desensitization. As expected, MOR363D, missing the putative agonist-induced phosphorylation sites, did not exhibit detectable agonist-induced phosphorylation. MOR363D underwent slower internalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 37 publications
(29 reference statements)
1
24
0
Order By: Relevance
“…GRKs overexpression was the most commonly used method to study the effect of phosphorylation on receptor desensitization [33,40]. In order to overcome the difficulties in correlating the phosphorylation states of the receptor and desensitization, previous report has investigated the effect of receptor phosphorylation on desensitization by eliminating the putative phosphorylation sites in OPRM1 [41]. However, involvement of receptor phosphorylation in rapid desensitization was still unclear, since the relatively long agonist pretreated time and high agonist concentration resulted in OPRM1 desensitization rate reflecting both the uncoupling of OPRM1 from the G-protein and the internalization of OPRM1.…”
Section: Discussionmentioning
confidence: 99%
“…GRKs overexpression was the most commonly used method to study the effect of phosphorylation on receptor desensitization [33,40]. In order to overcome the difficulties in correlating the phosphorylation states of the receptor and desensitization, previous report has investigated the effect of receptor phosphorylation on desensitization by eliminating the putative phosphorylation sites in OPRM1 [41]. However, involvement of receptor phosphorylation in rapid desensitization was still unclear, since the relatively long agonist pretreated time and high agonist concentration resulted in OPRM1 desensitization rate reflecting both the uncoupling of OPRM1 from the G-protein and the internalization of OPRM1.…”
Section: Discussionmentioning
confidence: 99%
“…However, experiments with C-terminal chimeras or truncations of the -and ␦-opioid receptors revealed that the C-tail cannot be the only region involved in receptor regulation (35)(36)(37)(38). It is further questionable whether a MOPr-derived endocytic recycling sequence (MRS) recently identified in the C terminus of -opioid receptors (39) is in fact essential for inducing receptor recycling because the C-terminal MOPr splice variants (MOPr-B and MOPr-D), which lack the MRS motif, undergo faster agonist-induced endocytosis and recycling than MOPr (40).…”
Section: Discussionmentioning
confidence: 99%
“…An important mechanism that regulates this process is termed receptor desensitization, which results in a reduction in the rate of G protein activation by the agonist-bound receptor complex (5,6). Desensitization is thought to be mediated through phosphorylation by G protein-coupled receptor kinases (GRKs) and second messenger-dependent protein kinases such as cAMP-dependent kinase (PKA), protein kinase C (PKC), and calmodulin-dependent kinase (7)(8)(9)(10)(11). Only GRKs selectively phosphorylate agonist-activated receptors, whereas second messenger-dependent kinases can phosphorylate receptors in the presence or absence of agonist.…”
mentioning
confidence: 99%